Religious tourism: devotion or business opportunity? - Carvalho, Aida (2013)
Religious tourism can be understood as an activity in which people travel either for worshipping purposes or to participate in events of religious significance. It can be seen as an alternative to mass tourism activities, aiming for specific targets. Portugal has a significant and rich religious heritage which can help to revitalize traditionally neglected rural areas. The active participation of the Church is of utmost importance as far as the visitors are concerned. On one hand it should assure the maintenance of the places´ main functions and religious features. On the other it should prevent this type of activity to become related to mass tourism loosing therefore its essence. This case study focuses on the analysis of the individual’s profile who visits religious places, having in mind the national statistics. It is complemented by a practical study with individuals who participate in Nossa Senhora dos Remédios festivity, in Lamego on September 8th. 196 questionnaires were elaborated and completed in order to understand the motivations that lie behind religious tourism. This analysis can add some valuable information to the people or institutions in charge of religious policies, when it comes to develop the most suitable strategies to the local context, so that the modern approach of the monument coexists with its religious function in perfect harmony. Keywords: Devotion, Religious tourism, Sanctuary.